Analisis Perbandingan Strategi Promosi pada Marketplace Shopee dan Lazada - nurfadillah; Haryanti, intisari; M Syukur Dwiriansyah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
The Promotion Strategy is a step in the field of marketing in the form of interaction/communication carried out by the company with consumers or customers. The interactions that are formed in the marketing promotion strategy are in the form of providing information, inviting, and giving influence about a product. The purpose of this research is to find out whether there are differences in promotional strategies between shopee and lazada. The population in this study were all shopee and lazada consumers in Bima City and the sample used in this study was 100 samples which were divided into 50 shopee respondents and 50 lazada respondents. The sampling technique uses purposive sampling. The analysis technique uses the independent t-test. The results of the research show that there are differences in promotion strategies on the marketplace, Shopee and Lazada